2018
DOI: 10.1096/fj.201800120r
|View full text |Cite
|
Sign up to set email alerts
|

Novel prognostic and predictive microRNA targets for triple‐negative breast cancer

Abstract: Triple-negative breast cancers (TNBCs) account for ∼25% of all invasive carcinomas and represent a large subset of aggressive, high-grade tumors. Despite current research focused on understanding the genetic landscape of TNBCs, reliable prognostic and predictive biomarkers remain limited. Although dysregulated microRNAs (miRNAs) have emerged as key players in many cancer types, the role of miRNAs in TNBC disease progression is unclear. We performed miRNA profiling of 51 TNBCs by next-generation sequencing to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 87 publications
3
53
0
Order By: Relevance
“…Mounting evidence shows that miR‐30a‐5p represses tumour progression by targeting E2F7 or IGF1R . Reduced expression of miR‐30a‐5p is a poor indicator in breast cancer . In accordance, we found that miR‐30a‐5p was down‐regulated in NSCLC tissues, and decreased expression of miR‐30a‐5p was associated with poor survival and tumour recurrence in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Mounting evidence shows that miR‐30a‐5p represses tumour progression by targeting E2F7 or IGF1R . Reduced expression of miR‐30a‐5p is a poor indicator in breast cancer . In accordance, we found that miR‐30a‐5p was down‐regulated in NSCLC tissues, and decreased expression of miR‐30a‐5p was associated with poor survival and tumour recurrence in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 79%
“…27 Reduced expression of miR-30a-5p is a poor indicator in breast cancer. 28 In accordance, we found that miR-30a-5p was down-regulated in NSCLC tissues, and decreased expression of miR-30a-5p was associated with poor survival and tumour recurrence in patients with NSCLC. PHTF2 was further identified as a direct target of miR-30a-5p in NSCLC cells and harboured a negative correlation with miR-30a-5p expression in NSCLC tissues.…”
Section: Discussionsupporting
confidence: 72%
“…A significant difference in the expression of miR-30a-3p in high invasive PTC (present lateral lymph node metastasis) compared to low invasive PTC (no lymph node metastasis), with a trend towards association with tumor multifocality was described [31]. In other types of cancer, miR-30a-3p downregulation was associated with advanced stage and more aggressive tumor features such as tumor size, pT category, nodal metastases, TNM stage in lung cancer [8], with higher tumor grade and poorer differentiation in ovarian cancer [16,42], vascular invasion in hepatocellular carcinoma [18], distant metastases in lung and renal carcinoma [43,44] and shorter progression free or overall survival in many of them [8,[11][12][13]28,42].…”
Section: Discussionmentioning
confidence: 96%
“…One of the microRNAs with potential tumor suppressor activity that is frequently found to be deregulated and associated with aggressive tumor features and progression in various human cancers is miR-30a-3p. So far, downregulated expression of this member of the miR-30 family has been reported in lung cancer [7][8][9][10], breast cancer [11][12][13], colorectal cancer [14], bladder cancer [15], ovarian cancer [16], endometrial cancer [17], hepatocellular carcinoma [18], hematologic malignancies [19] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, poly(A) enrichment was first performed using the NEBNext Poly(A) mRNA Magnetic Isolation Module (New England BioLabs, E7490). [57][58][59] The top 0.5% of ranked genes remaining after filtering were used in the unsupervised learning analysis. Paired-end sequencing was performed for each sample using the Illumina NextSeq 500 platform (Illumina, USA) with the NextSeq 500/550 High Output Kit v2 as the sequencing reagent.…”
Section: Neutrophil Next-generation Rna Sequencing and Associated Dmentioning
confidence: 99%